Using Powtoon Educational Videos to Enhance Interactive IPAS Learning - Oktoberiansyah; Siti Dewi Maharani; Syarifuddin (Universitas Pendidikan Ganesha, 2025)
Less interactive learning activities and teachers having difficulty developing interactive learning media have an impact on students' low mastery of concepts. This study aims to develop and implement educational video media based on Powtoon in learning the subject of Natural and Social Sciences (IPAS) for grade IV of elementary school with the aim of improving students' understanding of the material